Measuring the Performance of Saudi Domestic Airports Using Data Envelopment Analysis(DEA)" (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The following research is aimed at evaluating the performance of domestic airports in Saudi Arabia with the help of Data Envelopment Analysis (DEA), based on outputs and inputs of the airports . A total of 21 domestic airports in Saudi Arabia were evaluated. The inputs were represented by such variables as Total Airport Capacity, Operation Cost and Number of Routs, whereas Numbers of Movement, Passengers and Cargo were considered as outputs. According to the results of the research, only ten airports of those under study are purely technically efficient. Eleven airports were found inefficient. The Super efficiency model was used to conduct ranking of efficient airports.